Thermal and Frequency Response Analysis on Friction Stir Welding Tool with Different Materials by Using FEA Method - Pandey, Rohit (Journal of Welding and Joining, 2024)
Friction stir welding (FSW) is a solid-state joining technique that joins two facing workpieces without melting the workpiece material. It makes use of a deceased item. The region surrounding the FSW tool softens due to heat produced by friction between the revolving tool and the workpiece material. We are now working on specialised applications (lap and butt welding) while concentrating on test sorts. In addition to being faster than the state of the art, both provide lap welds that are 190% of the plate thickness, improve weld honesty, and lessen upper plate decline. Friction stir welding, or FSW for short, is a popular solid state joining method for soft materials like aluminium alloys. For stronger alloys like steel and titanium alloys, the FSW process's economic sustainability hinges on the creation of long-lasting, moderately cost equipment that reliably yields welds with outstanding structural integrity. The performance of the tool, weld quality, and cost are all impacted by material design and choice. This research reviews and critically examines many key FSW tool components, including process economics, geometry and load bearing capacity, frequency response analysis, tool degradation mechanisms, and tool material selection. The Finite Element Method (FEM) approach is used to characterise the process and provide a more comprehensive knowledge of the thermal effects and thermal inaccuracies on the tool materials.
uGDX
Keywords: Friction stir welding; Tool geometry; load bearing; Tool material; FEM